Với mọi \(0< a< \dfrac{1}{2}\) ta có:
\(\left(\sqrt{2a}-1\right)^2\ge0\Rightarrow2a+1\ge2\sqrt{2a}\)
\(\Rightarrow1\ge2\sqrt{a}\left(\sqrt{2}-\sqrt{a}\right)\)
\(\Rightarrow\dfrac{1}{\sqrt{2}-\sqrt{a}}\ge2\sqrt{a}\)
Do đó:
\(\dfrac{2+\sqrt{2a}}{2-a}=\dfrac{2-a+a+\sqrt{2a}}{2-a}=1+\dfrac{\sqrt{a}\left(\sqrt{a}+\sqrt{2}\right)}{\left(\sqrt{2}-\sqrt{a}\right)\left(\sqrt{2}+\sqrt{a}\right)}=1+\dfrac{\sqrt{a}}{\sqrt{2}-\sqrt{a}}\ge1+\sqrt{a}.2\sqrt{a}=2a+1\)
Tương tự:
\(\dfrac{2+\sqrt{2b}}{2-b}\ge2b+1\)
Cộng vế:
\(\dfrac{2+\sqrt{2a}}{2-a}+\dfrac{2+\sqrt{2b}}{2-b}\ge2a+1+2b+1=4\) (đpcm)
Dấu "=" xảy ra khi \(a=b=\dfrac{1}{2}\)